2019
DOI: 10.3390/dj7030090
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Zirconia: An Update to Current Knowledge. Optical Properties, Wear, and Clinical Performance

Abstract: The purpose of this paper was to update the knowledge concerning the wear, translucency, as well as clinical performance of monolithic zirconia ceramics, aiming at highlighting their advantages and weaknesses through data presented in recent literature. New ultra-translucent and multicolor monolithic zirconia ceramics present considerably improved aesthetics and translucency, which, according to the literature reviewed, is similar to those of the more translucent lithium disilicate ceramics. A profound advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 142 publications
1
104
1
6
Order By: Relevance
“…Thus, the second null hypothesis of the study was rejected. The growing success of the digital workflow is most likely also due to the development of monolithic materials to be milled using CAD/CAM technology, as they have demonstrated excellent biomechanical, biological and biomimetic properties [20,27]. Zirconia is a crystalline dioxide of zirconium that is the strongest ceramic used in restorative dentistry for the fabrication of single and multiple unit restorations (monolithic or veneered) in the anterior and posterior region.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the second null hypothesis of the study was rejected. The growing success of the digital workflow is most likely also due to the development of monolithic materials to be milled using CAD/CAM technology, as they have demonstrated excellent biomechanical, biological and biomimetic properties [20,27]. Zirconia is a crystalline dioxide of zirconium that is the strongest ceramic used in restorative dentistry for the fabrication of single and multiple unit restorations (monolithic or veneered) in the anterior and posterior region.…”
Section: Discussionmentioning
confidence: 99%
“…1) [3,7]. Zur Reduktion des Risikos technischer Komplikationen wurde bereits vor 10 Jahren mit der Entwicklung transluzenter Zirkonoxidkeramiken begonnen, die auch fĂźr die Herstellung monolithischer Restaurationen geeignet sind [8].…”
Section: Entwicklung Transluzenter Zirkonoxidkeramikenunclassified
“…The relative influencing factors in tooth surface wear opposing to ceramic restorations include the type, microstructure, surface roughness, and the mechanical properties of the material itself. For decades owing to their excellent mechanical properties; multiphase partially stabilized zirconia substructures veneered with feldspathic porcelain has been widely used [6][7][8][9][10][11][12]. However, it was reported that the chipping of this veneering may reach up to 40%, accompanied with further wear and fracture of opposing tooth enamel.…”
Section: Introductionmentioning
confidence: 99%